Diagnosis of construction and demolition waste management (CDW) in the city of Caruaru, Pernambuco - Gomes Júnior, Edmilson; Bello, Maria Isabela Marques da Cunha Vieira (Revista Nacional de Gerenciamento de Cidades, 2022)
The management of construction and demolition waste (CDW) is the main tool for construction housing sustainably. This article presents a diagnosis of the management of CDW and their environmental impacts in the municipality of Caruaru, Pernambuco. The construction and demolition waste management Index (CDWMI) was calculated. This index uses the environmental sustainability indicators: management instruments, management programs, collection and screening, and treatment and disposition of the CDW. The results of this research were compared with the results of six municipalities in the metropolitan region of Recife (MRR). The evaluation of the management of the municipality of Caruaru regarding the CDW indicated the low performance of the municipality since, of the four groups of instruments used, three of them were low grades, and only in the indicators of instruments for policies obtained the average grade. With the diagnosis of a low degree of sustainability in relation to the management of CDW, it is evident that there must be a restructuring in the management of the municipality so that what is established and agreed upon in the Municipal Solid Waste Plan (MSWP) is commenced.